Dual anti‐inflammatory and antiglycation propensities of a potentially novel class of functionalized fluoroquinolones. (5th November 2019) - Hamdan, Alaa; Kasabri, Violet; Al‐Hiari, Yusuf; Arabiyat, Shereen; AlAlawi, Sundus; Bustanji, Yasser
Abstract: Promoted by elevated blood glucose concentrations in diabetes, glycation involves the nonenzymatic addition of reducing sugars and/or their reactive degradation products to amine groups on proteins. New synthetic approaches to 18 fluoroquinolones (FQs) have been developed on the basis of a promising antiglycation activity using 400μM methylglyoxal as the choice glucocytotoxicity concentration. Their anti‐inflammatory and radical scavenging properties were elucidated in vitro. Intriguingly, FQs could exhibit an exceedingly more superior than or substantially comparable cytoprotection against methylglyoxal‐induced carbonyl toxicity in RAW264.7 macrophages and antiglycation activity to aminoguanidine, as the reference compound. This kind of activity can suggestively be associated with the chelating properties possessed by the synthesized FQs as their DPPH radical scavenging activities proved to be significantly inferior to those of the reference compound, the ascorbic acid. The inhibitory bioactivities using the Griess assay were examined of the compounds against lipopolysaccharide (LPS)‐induced nitric oxide (NO) production in RAW 264.7 macrophages. Selectively, compounds R‐2TCBA, R‐4FACBA, R‐3TCBA, and R‐4CLACBA exerted an exceedingly remarkable and superior anti‐inflammatory effects ( P  < .001 vs indomethacin IC50 value of 101.07 ± 2.2 μM) while R‐4TCBA and T‐4BrACBA were moderately more efficacious than indomethacin. Compounds T‐4CLACBA and R‐4BrACBA displayed comparable activity with indomethacin. None of the tested compounds and indomethacin exerted any cytotoxicity against RAW 264.7 mouse macrophages. FQs possess potent duality of antiglycation–anti‐inflammatory capacities and are devoid of undesirable side effects. FQs can, therefore, serve as scaffolds for the development and designing of new clinical deglycation and antiglycation therapeutic agents. Abstract :